Tannat grape pomace as an ingredient for potential functional biscuits: bioactive compound identification, in vitro bioactivity, food safety, and sensory evaluation - Olt, Victoria; Báez, Jessica; Curbelo, Romina; Boido, Eduardo; Amarillo, Miguel; Gámbaro, Adriana; Alborés, Silvana; Gerez García, Natalia; Cesio, María Verónica; Heinzen, Horacio; Dellacassa, Eduardo; Fernández-Fernández, Adriana Maite; et al. (Frontiers in Nutrition, 2023)
Grape pomace, the main byproduct of wine process, shows high potential for the development of functional foods, being a natural source of bioactive compounds and dietary fiber. Thus, the present study proposes the development of 5 potential functional biscuits by varying the Tannat grape pomace powder (TGP, 10-20% w/w total wet dough) and sweetener sucralose (2-4% w/w total wet dough) content. Identification of bioactive compounds by HPLC-DAD-MS, in vitro bioactivity and sensory properties of the biscuits were evaluated. Previously, TGP microbiological and pesticides were evaluated showing values within food safety criteria. Sensory profiles of TGP biscuit formulations were obtained, showing biscuits with 20% TGP good sensory quality (7.3, scale 1-9) in a cluster of 37 out of 101 consumers. TGP addition in biscuits had a significant (p<0.05) effect on total phenolic content (0.893-1.858 mg GAE/g biscuit) and the evaluated bioactive properties when compared to controls: antioxidant (11.467-50.491 and 4.342-50.912 µmol TE/g biscuit for ABTS and ORAC-FL, respectively), antidiabetic and antiobesity (inhibition of α-glucosidase and pancreatic lipase, IC50 35.572-64.268 and 7.197-47.135 mg/mL, respectively). HPLC-DAD-MS results showed all the identified phenolic compounds in 20/4% biscuit (TGP/sucralose%) were degraded during the biscuits’ baking. Malvidin-3-O-(6'-p-coumaroyl) glucoside, (+)-catechin, malvidin-3-O-glucoside, and (-)-epicatechin were the main phenolic compounds (in descendent order of content) found. The bioactive properties could be attributed to the remaining phenolic compounds in the biscuits. In conclusion, TGP biscuits seemed to be a promising functional food with potential for ameliorating oxidative stress, glucose and fatty acids levels with good sensory quality.